Policy networks in comparative politics and international relations: perspectives, typologies and functions - Anja P. Jakobi (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
In this paper, I review existing approaches to network analysis in comparative politics and International Relations (IR). I argue that the theoretical and empirical exploration of global policy networks in IR today can benefit from systematically taking into account the literature that has emerged in comparative politics in the 1980s and 1990s. To show the relationship between both fields, I compare three aspects in research linked to networks, namely the analytical perspectives from which networks are examined, network typologies, and the functions of networks. Finally, I outline three areas that are likely to enrich future IR research on networks: interest representation in networks, typologies of global policy networks and the methodology linked to their inquiry – – Dieses Papier präsentiert Netzwerkonzeptionen in der Vergleichenden Politikwissenschaft und den Internationalen Beziehungen (IB). Es stellt die These auf, dass IB Forschung davon profitieren kann, die Netzwerk-Forschung der Vergleichenden Politikwissenschaft systematischer zu nutzen. Um die beiden Forschungsstränge gegenüber zu stellen, vergleiche ich drei Aspekte der Netzwerkforschung: a) die analytischen Perspektiven auf Netzwerke; b) Netzwerk-Typologien und c) Netzwerk-Funktionen. Abschließend skizziere ich Bereiche, die für die IB Forschung zu Netzwerken besonders interessant sind, insbesondere die Interessenvertretung in globalen Netzwerken, Typologien globaler Politiknetzwerke und die methodische Weiterentwicklung der Forschung zu diesen Netzwerken.
Keywords: 320; Internationale Beziehungen; Policy-Ansatz; Netzwerk